Validation of genome-wide association study-identified single nucleotide polymorphisms in a case-control study of pancreatic cancer from Taiwan - Yan-Shen Shan; Li-Tzong Chen; Jin-Shang Wu; Yin-Fan Chang; Chih-Ting Lee; Chih-Hsing Wu; Nai-Jung Chiang; Hsin-En Huang; Chia-Jui Yen; Ying-Jui Chao; Hui-Jen Tsai; Chiung-Yu Chen; et al. (Journal of Biomedical Science, 2020)
Abstract Background Due to differences in genetic background, it is unclear whether the genetic loci identified by the previous genome-wide association studies (GWAS) of pancreatic cancer also play significant roles in the development of pancreatic cancer among the Taiwanese population. Methods This study aimed to validate the 25 pancreatic cancer GWAS-identified single nucleotide polymorphisms (SNPs) in a case-control study (278 cases and 658 controls) of pancreatic cancer conducted in Taiwan. Statistical analyses were conducted to determine the associations between the GWAS-identified SNPs and pancreatic cancer risk. Gene-environment interaction analysis was conducted to evaluate the interactions between SNPs and environmental factors on pancreatic cancer risk. Results Among the 25 GWAS-identified SNPs, 7 (rs2816938 (~ 11 kb upstream of NR5A2), rs10094872 (~ 28 kb upstream of MYC), rs9581943 (200 bp upstream of PDX1) and 4 chromosome 13q22.1 SNPs: rs4885093, rs9573163, rs9543325, rs9573166) showed a statistically significant association with pancreatic cancer risk in the current study. Additional analyses showed two significant gene-environment interactions (between poor oral hygiene and NR5A2 rs2816938 and between obesity and PDX1 rs9581943) on the risk of pancreatic cancer. Conclusions The current study confirmed the associations between 7 of the 25 GWAS-identified SNPs and pancreatic risk among the Taiwanese population. Furthermore, pancreatic cancer was jointly influenced by lifestyle and medical factors, genetic polymorphisms, and gene-environment interaction. Additional GWAS is needed to determine the genetic polymorphisms that are more relevant to the pancreatic cancer cases occurring in Taiwan.